2005
DOI: 10.1007/s11738-005-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Lignin content and peroxidase activity in soybean seed coat susceptible and resistant to mechanical damage

Abstract: Key words: ge netic vari abil ity, lignothioglycolic acid, pro tein-free lignin, soy bean cultivars Ab stractMe chan i cal dam age is one of the causes of great loss in the qual ity of soy bean seeds dur ing har vest and pro cess ing. Consid er able in ter est ex ists in the lignin since its de po si tion in the seed coat tis sue pro vides me chan i cal re sis tance and pro tects the cell against mi cro or gan isms. In ad di tion, peroxidases might be in volved in the ox i da tion of cinnamyl al co hols prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Seed elasticity plays an important role in the first stage of crushing, and its viscosity -in the subsequent stages (Dobrzański, Stępniewski, 2013). The occurrence of damage also depends on the size and shape of seeds as well as seed coat thickness and chemical composition (Capeleti et al, 2005;Rybiński et al, 2013). Karaj and Müller (2010) and Dobrzański and Stępniewski (2013) demonstrated that seed resistance to mechanical damage significantly decreases together with an increase in seed weight.…”
Section: Introductionmentioning
confidence: 99%
“…Seed elasticity plays an important role in the first stage of crushing, and its viscosity -in the subsequent stages (Dobrzański, Stępniewski, 2013). The occurrence of damage also depends on the size and shape of seeds as well as seed coat thickness and chemical composition (Capeleti et al, 2005;Rybiński et al, 2013). Karaj and Müller (2010) and Dobrzański and Stępniewski (2013) demonstrated that seed resistance to mechanical damage significantly decreases together with an increase in seed weight.…”
Section: Introductionmentioning
confidence: 99%
“…As the main structural component of secondarily thickened plant cell walls, lignin contributes to the compression strength of stems to provide mechanical support (Boudet 2000;Boudet et al 2003) and to the efficient transport of water and solutes over long distances within the vascular system (Bernards et al 2000;Donaldson 2001). Lignin in seed coat tissues provides resistance against mechanical damage and protects the cell from microbial attack (Capeleti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin derives from the dehydrogenative polymerization of three different hydroxycinnamyl alcohols, p-coumaryl alcohol, conferyl alcohol and sinapyl alcohol (Ma 2007), which was believed to play an important role in cell wall thickening and stress response (Kuc 1997;Solecka 1997;Kaczkowski 2003;Capeleti et al 2005). So far, it is generally accepted that cinnamoyl CoA reductase (CCR, EC 1.2.1.44) catalyzes the first specific step reaction in lignin monomers synthesis, converting cinnamoyl CoA esters to their corresponding cinnamaldehydes.…”
Section: Introductionmentioning
confidence: 99%